Betaine and Trimethylamine-N-Oxide as Predictors of Cardiovascular Outcomes Show Different Patterns in Diabetes Mellitus: An Observational Study - Lever, Michael; George, Peter M.; Slow, Sandy; Bellamy, David; Young, Joanna M.; Ho, Markus; McEntyre, Christopher J.; Elmslie, Jane L.; Atkinson, Wendy; Molyneux, Sarah L.; Troughton, Richard W.; Frampton, Christopher M.; et al. (PLOS ONE, 2014)
Background Betaine is a major osmolyte, also important in methyl group metabolism. Concentrations of betaine, its metabolite dimethylglycine and analog trimethylamine-N-oxide (TMAO) in blood are cardiovascular risk markers. Diabetes disturbs betaine: does diabetes alter associations between betaine-related measures and cardiovascular risk? Methods Plasma samples were collected from 475 subjects four months after discharge following an acute coronary admission. Death (n = 81), secondary acute MI (n = 87), admission for heart failure (n = 85), unstable angina (n = 72) and all cardiovascular events (n = 283) were recorded (median follow-up: 1804 days). Results High and low metabolite concentrations were defined as top or bottom quintile of the total cohort. In subjects with diabetes (n = 79), high plasma betaine was associated with increased frequencies of events; significantly for heart failure, hazard ratio 3.1 (1.2–8.2) and all cardiovascular events, HR 2.8 (1.4–5.5). In subjects without diabetes (n = 396), low plasma betaine was associated with events; significantly for secondary myocardial infarction, HR 2.1 (1.2–3.6), unstable angina, HR 2.3 (1.3–4.0), and all cardiovascular events, HR 1.4 (1.0–1.9). In diabetes, high TMAO was a marker of all outcomes, HR 2.7 (1.1–7.1) for death, 4.0 (1.6–9.8) for myocardial infarction, 4.6 (2.0–10.7) for heart failure, 9.1 (2.8–29.7) for unstable angina and 2.0 (1.1–3.6) for all cardiovascular events. In subjects without diabetes TMAO was only significant for death, HR 2.7 (1.6–4.8) and heart failure, HR 1.9 (1.1–3.4). Adding the estimated glomerular filtration rate to Cox regression models tended to increase the apparent risks associated with low betaine. Conclusions Elevated plasma betaine concentration is a marker of cardiovascular risk in diabetes; conversely low plasma betaine concentrations indicate increased risk in the absence of diabetes. We speculate that the difference reflects control of osmolyte retention in tissues. Elevated plasma TMAO is a strong risk marker in diabetes.